Simultaneous abrupt shifts in hydrology and fish assemblage structure in a floodplain lake in the central Amazon - Röpke, Cristhiana Paula; Amadio, Sidineia Aparecida; Zuanon, Jansen; Ferreira, Efrem J.G.; Deus, C. P.; Pires, Tiago H.S.; Winemiller, Kirk O. (Scientific Reports, 2017)
Combined effects of climate change and deforestation have altered precipitation patterns in the Amazon. This has led to changes in the frequency of extreme events of flood and drought in recent decades and in the magnitude of the annual flood pulse, a phenomenon that influences virtually all aspects of river-floodplain ecosystem dynamics. Analysis of long-term data revealed abrupt and synchronous changes in hydrology and fish assemblage structure of a floodplain lake near the confluence of Amazon and Negro rivers. After an intense drought in 2005, the assemblage assumed a different and fairly persistent taxonomic composition and functional structure. Declines in abundance after 2005 were more pronounced for species of all sizes having equilibrium life history strategy, large species with periodic life history strategy, and for all trophic levels except primary consumers. Our results suggest that the extreme drought triggered changes in the fish assemblage and subsequent anomalous hydrological conditions have hampered assemblage recovery. These findings stress the need to account for climatic-driven hydrological changes in conservation efforts addressing aquatic biodiversity and fishery resources in the central Amazon. © The Author(s) 2017.
Keywords: Biodiversity; Consumer; Drought; Fishery; Floodplain; Human; Hydrology; Life History; Species; Stress; Structure Activity Relation; Trophic Level; Animals; Biota; Classification; Climate Change; Environmental Protection; Fish; Flooding; Growth, Development And Aging; Lake; Longitudinal Study; River; Water Cycle; Animal; Biota; Climate Change; Conservation Of Natural Resources; Fishes; Floods; Lakes; Longitudinal Studies; Rivers; Water Cycle